2009
DOI: 10.1016/j.nucmedbio.2009.02.004
|View full text |Cite
|
Sign up to set email alerts
|

[186Re]Liposomal doxorubicin (Doxil): in vitro stability, pharmacokinetics, imaging and biodistribution in a head and neck squamous cell carcinoma xenograft model

Abstract: The purpose of this study was to determine the feasibility of radiolabeling liposomal doxorubicin (Doxil) for cancer chemoradionuclide therapy by directly loading the therapeutic radionuclide rhenium-186 ((186)Re) into the liposome interior. The pharmacokinetics, imaging and biodistribution of [(186)Re]Doxil (555 MBq/kg) and control [(186)Re]polyethylene glycol (PEG) liposomes (555 MBq/kg) were determined after intravenous administration in a head and neck cancer xenograft model in nude rats. [(186)Re]Doxil an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 39 publications
2
84
2
Order By: Relevance
“…33,34 The labeling efficiency, in vitro stability, pharmacokinetics, and biodistribution of 186 Re-Doxil and 186 Re-PEG-liposomes have been previously evaluated. 35 Control PEG-liposomes were prepared with similar lipid composition, ammonium sulfate gradient, and diameter as Doxil. The results of the study revealed that 186 Re-Doxil and 186 Re-PEG-liposomes had similar in vitro stability but 186 Re-Doxil had a circulation time of 28.2 hours and 186 Re-PEG-liposomes were rapidly cleared from circulation by liver and spleen.…”
mentioning
confidence: 99%
“…33,34 The labeling efficiency, in vitro stability, pharmacokinetics, and biodistribution of 186 Re-Doxil and 186 Re-PEG-liposomes have been previously evaluated. 35 Control PEG-liposomes were prepared with similar lipid composition, ammonium sulfate gradient, and diameter as Doxil. The results of the study revealed that 186 Re-Doxil and 186 Re-PEG-liposomes had similar in vitro stability but 186 Re-Doxil had a circulation time of 28.2 hours and 186 Re-PEG-liposomes were rapidly cleared from circulation by liver and spleen.…”
mentioning
confidence: 99%
“…In previous studies, it was found that particles in the range of 60-400 nm extravasate and accumulate in tumors via a passive mechanism, called 'enhanced permeability and retention (EPR)' effect. 22 Accordingly, the size of MDC (60-70 nm) or Doxil (80-90 nm) 7 are in the suitable range for inducing the EPR effect. However, only particles in the range of 30 nm in diameter could penetrate into poorly permeable pancreatic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…7 Doxil is a drug of doxorubicin (Dox) confined in liposomes that is sterically stabilized by grafting polyethylene glycol onto the surface [pegylated liposomal doxorubicine (PLD)]. PLD has a circulation half-life of 73.9 hours, whereas Dox has a short half-life of less than 10 min.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Figure 2Q-R show that also for radiolabeled Doxil, (i.e. PEGylated liposomal doxorubicin), EPR-mediated passive drug targeting to tumors can be visualized and quantified, both in nude rats bearing head-and-neck cancer xenografts ( Figure 2Q), and in patients suffering from different types of sarcomas ( Figure 2R) [51,52].…”
Section: Theranostic Nanomedicinementioning
confidence: 99%
“…from different types of sarcomas (R), thereby enabling patient preselection and (more) personalized nano-chemotherapeutic treatments. Images are adapted, with permission, from [30,[32][33][34][38][39][40][41][42][50][51][52]. Rationale for image-guided and personalized nanomedicine.…”
Section: Theranostic Nanomedicinementioning
confidence: 99%